2021
DOI: 10.1109/tnsre.2021.3107780
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Activity Recognition With Instantaneous Characteristic Features of Thigh Kinematics

Abstract: Current supervised learning or deep learning-based activity recognition classifiers can achieve high accuracy in recognizing locomotion activities. Most available techniques use a high-dimensional space of features, e.g., combinations of EMG, kinematics and kinetics, and transformations over those signals.The associated classification rules are therefore complex; the machine tries to understand the human, but the human does not understand the machine. This paper presents an activity recognition system that use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…This is particularly problematic during discrete transitions between steep inclines and level ground walking because the heelstrike kinematics vary drastically [24]. Future work involving anticipatory algorithms that update the task estimate based on sensed characteristics of the upcoming terrain [76]- [78] or user behavior [79], [80] may be necessary to alleviate this limitation.…”
Section: B Limitations and Future Workmentioning
confidence: 99%
“…This is particularly problematic during discrete transitions between steep inclines and level ground walking because the heelstrike kinematics vary drastically [24]. Future work involving anticipatory algorithms that update the task estimate based on sensed characteristics of the upcoming terrain [76]- [78] or user behavior [79], [80] may be necessary to alleviate this limitation.…”
Section: B Limitations and Future Workmentioning
confidence: 99%
“…These results demonstrate that real-time HAR could be performed for the wearable robot using a standalone system. Among the mentioned HAR works based on edge devices, the best approach was recently addressed in [24]. In this study, a HAR approach was reported based on a Raspberry Pi 3 board as an application for a wearable robot or leg prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…These mentioned approaches were tested using a Raspberry Pi 3 board with embedded lightweight machine classification models such as k-nearest neighbors (KNN), convolutional neural networks (CNN), and recurrent neural networks (RNN). Despite the significant use of deep learning models for activity recognition, few studies still use traditional machine-learning methods for real-time HAR environments in edge devices [24]. More than three IMU sensors were used to recognize the lower and upper limb activities such as walk, run, jog, and open doors.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly problematic during discrete transitions between steep inclines and level ground walking because the heelstrike kinematics vary drastically [24]. Future work involving anticipatory algorithms that update the task estimate based on sensed characteristics of the upcoming terrain [75]- [77] or user behavior [78], [79] may be necessary to alleviate this limitation.…”
Section: B Limitations and Future Workmentioning
confidence: 99%